Bashky: addressing, mentoring, and social relations - Lamazhaa, Chimiza K.; Kairzhanova, Adiya T. (The New Research of Tuva, 2025)
The article provides a comprehensive analysis of the tradition of “bashky” in Tuvan culture. “Bashky” is examined as a cultural concept from three perspectives: (1) its meaning as a term in the Tuvan language, (2) its multifaceted semantic content, and (3) its socially regulatory function. This approach investigates what Tuvans articulate, think about, and are guided by in their actions. The etymology of the word reveals cultural roots in the Chinese tradition of mentorship. The history of this tradition is also linked to the Buddhist understanding and veneration of teachers. Mentorship as a tradition adapted to Tuvan culture, transferring the religious notion of a Buddhist teacher to general education, and became embedded in folklore. The concept also introduced a new dimension to social relations, fostering teacher-student dynamics beyond traditional societal roles. During the Soviet era, the term “bashky” was primarily used in the context of professional pedagogical activity and referred to teachers. This interpretation persists to this day. However, the original meanings of the word “bashky” have been preserved in the Tuvan language and beyond. Numerous examples of the use of the term “bashky” by Tuvans throughout the 20th century and into the present confirm this continuity. Tuvans actively use the term “bashky” as a form of address, signifying their acceptance of a hierarchical social structure. This hierarchy moves strictly upward — from the student to the teacher — in the form of voluntary recognition of the teacher’s status and expression of their intellectual and moral-spiritual superiority.